2003
DOI: 10.1029/2002tc001381
|View full text |Cite
|
Sign up to set email alerts
|

Formation of the Maturín Foreland Basin, eastern Venezuela: Thrust sheet loading or subduction dynamic topography

Abstract: The Maturín Basin in eastern Venezuela is considered a good example of a peripheral foreland basin. Earthquake and tomographic data indicate that eastern Venezuela is affected by the oblique subduction of the South American Plate underneath the Caribbean Plate. New forward flexural isostatic modeling of eastern Venezuela has been carried out in order to determine whether the Maturín Basin was generated purely by thrust sheet loading from the Serranía and Monagas Foreland Thrust Belts. A sequence of forward mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 23 publications
3
34
1
Order By: Relevance
“…They found that significant vertical displacements can derive from flexural bulging, asthenospheric flow, and viscous coupling with the subducting slab. Jácome et al [2003] demonstrated that thrust sheet loading could only account for 55% of the subsidence of the Maturin Basin, calculated using 96 km of shortening beneath the Serrania del Interior and foothills. Shortening of only 35 km onshore implies that basin subsidence due to thrust sheet loading is significantly less than 50%.…”
Section: Orogenesis and Basin Subsidence Without Significant Shorteningmentioning
confidence: 99%
See 2 more Smart Citations
“…They found that significant vertical displacements can derive from flexural bulging, asthenospheric flow, and viscous coupling with the subducting slab. Jácome et al [2003] demonstrated that thrust sheet loading could only account for 55% of the subsidence of the Maturin Basin, calculated using 96 km of shortening beneath the Serrania del Interior and foothills. Shortening of only 35 km onshore implies that basin subsidence due to thrust sheet loading is significantly less than 50%.…”
Section: Orogenesis and Basin Subsidence Without Significant Shorteningmentioning
confidence: 99%
“…South of the frontal thrust of the Monagas Foothills, the Maturin Basin, generally regarded as a peripheral foreland basin, formed concurrently with the thrust belts of the Serrania del Interior [Passalacqua et al, 1995;Roure et al, 1994]. However, thrust sheet loading alone does not adequately account for the 10 km of subsidence [Jácome et al, 2003]. The Maturin Basin is the southernmost region imaged by 64W.…”
Section: Geologic Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…[49] used seismic refraction data to estimate a maximum of 10-13 km of sedimentary infill for this basin. According to Jácome et al [14], the amount of sediments is the result of multiple processes: (a) flexural loading of the Cordillera de la Costa range, (b) large and continuous deposition of continental material from the Guyana shield as the main source, and (c) the subduction dynamics of oceanic South America underneath the Caribbean plate. The spectral analysis of the Bouguer anomaly (Figure 6(d)) estimated an anomaly source located 12 km deep that may correspond to the top of the basin basement.…”
Section: Regional and Residual Gravity Anomalies And Their Correlatiomentioning
confidence: 99%
“…Barinas-Apure is mainly a foreland basin generated by the flexural response to the Mérida-Andes Mountain load [13]. On the other hand, the Eastern basin can be considered to be the result of (a) flexural loading of the Cordillera de la Costa range, (b) large and continuous deposition of continental material from the Guyana shield, and (c) subduction dynamics in the east [14]. The Barinas-Apure and Eastern Venezuelan sedimentary basins are separated by a geomorphologic-structural high called El Baúl High, formed by an igneous-metamorphic complex.…”
Section: Geological Settingmentioning
confidence: 99%